c-Met inhibitors - Mughal, Anum (BioMed Central, 2013)
c-Met is a receptor tyrosine kinase that encodes protein such as hepatocyte growth factor receptor (HGFR). Inappropriate activity of c-Met can cause wide variety of carcinomas. c-Met inhibitor are relatively new class of small molecules that inhibit the enzymatic activity of c-Met tyrosine kinase. Met inhibitors divided into two main classes: class I (SU-11274-like) and class II (AM7-like). The use of c-Met inhibitors with other therapeutic agents could be crucial for overcoming potential resistance as well as for improving overall clinical benefit. Met pathway inhibitors might be used in combination with other treatments, including chemo-, radio- or immunotherapy